Renewable Energy and Economic Growth in the United Arab Emirates: A Causal Analysis of CO2 Emissions and Environmental Policy Trends - Sahal, Mastora Sahal Gomaa; Ahmad , Zaki; Ali , Mohamed Ali; Yousif , Nuseiba Azzam Ibrahim; Mohammed, Ali Alhag Ali; Mahade , Ahmed (International Journal of Energy Economics and Policy, 2025)
United Arab Emirates rapid economic expansion, environmental degradation, particularly CO₂ emissions, has emerged as a pressing challenge. The study explores the dynamic relationship between the utilization of renewable energy sources, CO₂ emissions, environmental policy, and economic growth over the period 2000–2023. Applied to yearly time-series data using Granger causality tests and the Autoregressive Distributed Lag (ARDL) model, the research identifies both immediate and long-term variations in equilibrium among the variables. The stationary nature of the variables at the first difference or degree was validated by the Augmented Dickey-Fuller (ADF) test, satisfying ARDL prerequisites. Testing for ARDL boundaries showed considerable long-term cointegration, demonstrating how these variables change in tandem over time. GDP is positively impacted by using renewable energy in a statistically significant way over the long run (coefficient = 0.275) and short term (coefficient ≈ 0.112), according to the data. CO₂ emissions exert a negative influence on long-term economic growth (coefficient ≈ –0.190). Environmental policy contributes positively to growth, reinforcing the role of governance in green transitions. Granger causality analysis further confirms that renewable energy and environmental policy unidirectionally influence GDP, whereas GDP and CO₂ emissions share a bidirectional feedback loop. These results highlight the crucial role of sustainable energy strategies and regulatory frameworks in supporting long-term economic resilience. For policymakers, the study offers actionable insights into how green investments and emission controls can reinforce development goals. Future research should consider sector-level disaggregation and integrate high-frequency or regional comparative datasets to refine policy analysis and advance GCC-wide sustainability efforts.